Equipment to prevent, diagnose, and treat hypothermia: a survey of Norwegian pre-hospital services - Karlsen, Anders M (BioMed Central, 2013)
INTRODUCTION: Hypothermia is associated with increased morbidity and mortality in trauma patients and poses a challenge in pre-hospital treatment. The aim of this study was to identify equipment to prevent, diagnose, and treat hypothermia in Norwegian pre-hospital services. METHOD: In the period of April-August 2011, we conducted a survey of 42 respondents representing a total of 543 pre-hospital units, which included all the national ground ambulance services, the fixed wing and helicopter air ambulance service, and the national search and rescue service. The survey explored available insulation materials, active warming devices, and the presence of protocols describing wrapping methods, temperature monitoring, and the use of warm i.v. fluids. RESULTS: Throughout the services, hospital duvets, cotton blankets and plastic “bubble-wrap” were the most common insulation materials. Active warming devices were to a small degree available in vehicle ambulances (14%) and the fixed wing ambulance service (44%) but were more common in the helicopter services (58-70%). Suitable thermometers for diagnosing hypothermia were lacking in the vehicle ambulance services (12%). Protocols describing how to insulate patients were present for 73% of vehicle ambulances and 70% of Search and Rescue helicopters. The minority of Helicopter Emergency Medical Services (42%) and Fixed Wing (22%) units was reported to have such protocols. CONCLUSION: The most common equipment types to treat and prevent hypothermia in Norwegian pre-hospital services are duvets, plastic “bubble wrap”, and cotton blankets. Active external heating devices and suitable thermometers are not available in most vehicle ambulance units.